Silk fibroin doped tannic acid-polyvinyl alcohol tissue bonding gel as well as preparation method and application thereof

By preparing silk fibroin-doped tannic acid-polyvinyl alcohol tissue adhesive gel, combined with gentamicin sulfate and growth factors, the problems of poor flexibility and high cytotoxicity of existing tissue adhesives were solved, achieving rapid wound healing and antibacterial effects, and possessing good mechanical properties and biocompatibility.

CN119280460APending Publication Date: 2025-01-10ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411184882.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing chemically synthesized tissue adhesives have problems such as poor flexibility, poor heat dissipation, high cytotoxicity, and compression of surrounding blood vessels and nerves during wound healing. In addition, traditional methods require high operational skills and cannot quickly seal wounds.

Method used

A tissue adhesive gel made of silk fibroin-doped tannic acid-polyvinyl alcohol (SF/TA-PVA) was developed. By loading gentamicin sulfate and basic fibroblast growth factor, a gel with a nanofiber structure was formed. Combining the hydrophilicity of PVA and the modification of SF/TA, rapid wound healing and antibacterial effects were achieved.

Benefits of technology

The tissue adhesive gel exhibits good stability at 37°C, excellent mechanical properties and biodegradability, rapid bactericidal effect, promotes cell proliferation and new tissue formation, and is simple and safe to use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119280460A_ABST
    Figure CN119280460A_ABST
Patent Text Reader

Abstract

The invention discloses silk fibroin doped tannic acid-polyvinyl alcohol tissue bonding gel as well as a preparation method and application thereof. The tissue bonding gel prepared by the invention can be gelled within 5 minutes and shows soft and strong tissue adhesion, and nanofibers are found in the structure. The preparation method comprises the following steps: dissolving tannic acid (TA) powder, dropwise adding into a silk fibroin (SF) solution to form a silk fibroin doped tannic acid (SF / TA) mixed solution, preserving at-80 DEG C, freeze-drying, and grinding into powder. And uniformly mixing a polyvinyl alcohol (PVA) solution loaded with gentamicin sulfate (Gen) and basic fibroblast growth factors (bFGF) with the SF / TA powder in proportion, wherein the SF / TA and the PVA are combined in a hydrogen bond mode in the mixing process to immediately form gel with good biological adhesion, and the gel has the potential of promoting formation of new tissues and resisting bacteria.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a composite material, and in particular to a silk fibroin doped tannic acid-polyvinyl alcohol (SF / TA-PVA) tissue adhesive gel and a preparation method and application thereof, which can be widely used in the fields of biology and medicine. Background Art

[0002] More than 312.9 million surgeries are performed worldwide each year. Currently, postoperative wound repair mainly uses staples, sutures and rivets. However, these methods still have many disadvantages and limitations, such as causing secondary damage and secondary infection to surrounding tissues, and failing to quickly isolate gas and liquid from the wound. In addition, many patients develop wound infection and scar formation after suturing, which leads to a long time for wound healing. Therefore, surgeons need to have good operating skills.

[0003] Tissue adhesive gel has many advantages such as less trauma, easy operation, and suitable for irregular-shaped wounds. It is the preferred material to replace closed sutures. In past studies, some researchers have developed materials with tissue adhesion, promoting wound healing, and easy operation, such as carboxymethyl chitosan, polyethylene glycol, gelatin, and sodium alginate.

[0004] Although tissue adhesive gel has been used clinically for many years, it still has some limitations and shortcomings. Commercial tissue adhesive products, such as n-butyl cyanoacrylate, 2-isooctyl cyanoacrylate and 2-isooctyl cyanoacrylate, have strong tissue adhesion and can act quickly on wounds, but still have some disadvantages, including poor flexibility, poor heat dissipation and high cytotoxicity. In addition, the release of formaldehyde leads to slow formation of new tissues and prolonged inflammation. Polyethylene glycol materials have good biocompatibility and water solubility, as well as safety, non-toxicity and certain antibacterial properties. Tissue adhesives of different molecular weights can be prepared by grafting and functionalization, and used as sealing and suturing aids for wound closure. However, the swelling volume will increase in an aqueous environment, which will squeeze the blood vessels and nerves around the tissue during tissue sealing or hemostasis, causing certain damage to the human body. Gelatin has good film-forming properties, excellent adhesion, foaming and emulsification. However, the commonly used cross-linking method for gelatin tissue adhesives is chemical cross-linking with aldehyde-containing materials, and some small molecule aldehydes such as glutaraldehyde have high cytotoxicity.

[0005] Tissue adhesive gels can be divided into three main types, including protein adhesive gels, polysaccharide adhesive gels, and synthetic polymer adhesive gels. Some studies have reported that protein polymer-based tissue adhesive gels have good biocompatibility and can promote new tissue formation because of their structure similar to the extracellular matrix. A few studies have shown that loading drugs or growth factors can prevent bacterial infection of wounds, induce new tissue formation, and accelerate wound healing. The release function of tissue adhesives can be modified by mixing with hydrophilic materials suitable for the early stages of wound healing. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of chemically synthesized tissue adhesives and to provide a silk fibroin-doped tannic acid tissue adhesive gel modified with polyvinyl alcohol and a preparation method and application thereof. The silk fibroin-doped tannic acid-polyvinyl alcohol tissue adhesive gel has good biocompatibility, good tissue adhesion, and has antibacterial and new tissue formation promoting effects.

[0007] In order to solve the technical problem, the present invention first provides a method for preparing a silk fibroin-doped tannic acid-polyvinyl alcohol tissue adhesive gel, which is characterized by comprising the following steps:

[0008] 1) preparing silk fibroin doped with tannic acid powder;

[0009] 2) PVA is dissolved in ultrapure water to prepare a PVA solution, and after the temperature is lowered, gentamicin sulfate Gen and basic fibroblast growth factor bFGF are added to the PVA solution respectively, and stirred until dissolved to prepare a PVA solution loaded with Gen and bFGF;

[0010] 3) The silk fibroin-doped tannic acid powder prepared in step 1) and the PVA solution loaded with Gen and bFGF prepared in step 2) are mixed at room temperature to obtain the desired SF / TA-PVA tissue adhesive gel.

[0011] According to a preferred embodiment of the present invention, the step 1) specifically comprises:

[0012] 1.1) Preparation of silk fibroin SF solution

[0013] SF powder is dissolved in ultrapure water and then released into SF solution;

[0014] 1.2) Preparation of tannic acid TA solution

[0015] TA powder was dissolved in ultrapure water and the pH value was adjusted to prepare TA solution;

[0016] 1.3) Preparation of silk fibroin doped with tannic acid SF / TA powder

[0017] The TA solution was added dropwise to the SF solution and the mixture was allowed to stand. After removing the excess TA, the mixture was freeze-dried and ground into SF / TA powder for later use.

[0018] According to a preferred embodiment of the present invention, in step 1.1), the concentration of the SF solution is 1.50-2.50 wt%.

[0019] According to a preferred embodiment of the present invention, in step 1.2), the concentration of the TA solution is 8-12 wt %, and the pH range is 5.50-6.50.

[0020] According to a preferred embodiment of the present invention, in step 1.3), the volume ratio of the TA solution to the SF solution is 1:1.20-1.30; and the standing time is 25-40 min.

[0021] According to a preferred embodiment of the present invention, the dissolution temperature of PVA is 75-85°C, the PVA solution is cooled to 37°C or below and then Gen and bFGF are added, the concentration of the PVA solution is 5-7wt%, the concentration of Gen in the PVA solution is 1-50mg / mL, and the concentration of bFGF in the PVA solution is 1-5ug / mL.

[0022] According to a preferred embodiment of the present invention, in step 3), the mass ratio of PVA to SF / TA powder in the solution is 1:33-83.

[0023] The invention also provides a silk fibroin-doped tannic acid-polyvinyl alcohol tissue adhesive gel prepared by the method.

[0024] The present invention also provides application of the silk fibroin doped with tannic acid-polyvinyl alcohol tissue adhesive gel in preparing a medicine for promoting wound tissue healing.

[0025] The silk fibroin used in the preparation process of the present invention is a natural protein biopolymer with the characteristics of low inflammatoryness, good biocompatibility, good biodegradability, good mechanical properties, etc. In addition, the U.S. Food and Drug Administration (FDA) has approved silk fibroin for use in biomedical fields such as tissue regeneration, suturing and drug carriers. SF fibers contain bioactive molecules such as RGD sequences, which are used to stimulate cell proliferation and tissue formation.

[0026] Tannic acid used in the preparation process of the present invention is a polyphenolic compound with hemostatic and anti-oxidation functions. FDA has approved tannic acid as a safe medicinal ingredient. The phenolic hydroxyl group of TA can form biological adhesion with other materials through hydrogen bonds or hydrophobic interactions. In addition, catechol and pyrogallol groups can modify proteins. For example, SF modified with TA shows the potential to form tissue adhesive glue. However, the combination of SF / TA will solidify rapidly after mixing with ultrapure water, and it is difficult to adjust the shape and fix it according to the size of the defect. In addition, the concentration of unbound TA in SF is still very high, which is slightly toxic to cells and reduces the cell proliferation ability.

[0027] The gel formed by mixing TA and PVA in the preparation process of the present invention has good biocompatibility and wound repair effect. The hydrophilic PVA can retain moisture during the wound healing process and accelerate the healing speed. In the early stage of wound healing, PVA can continuously release drugs or growth factors. After SF-TA is modified with PVA, the high degree of intramolecular interaction of SF-TA / PVA not only forms a flexible structure and nanofibers with stability, but also supports its application in any curve and fixation with defective wounds. In addition, the degree of crystal formation is high and the content of bound TA is low, thereby reducing the toxicity of tissue adhesive gel to cells.

[0028] In addition, the gentamicin sulfate (Gen) loaded by the present invention is an antibiotic drug that can effectively prevent Gram-negative and Gram-positive bacteria infections. Gentomycin sulfate can also induce the sericin fiber protein in the tissue adhesive gel to form a β-sheet structure, and the β-sheet structure can promote the mechanical properties and structural stability of long-term wound healing. The combined use of Gen and growth factors can promote the formation of new tissues and improve biological functions. In particular, the combined use of Gen and basic fibroblast growth factor (bFGF) can promote rapid and smooth healing of wounds. And their addition ratio is determined based on the safe concentration for the human body and the adhesion and stability of the tissue adhesive gel, because if the proportion of Gen is too low, the tissue adhesive gel will be in an unstable state.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The silk fibroin-doped tannic acid-polyvinyl alcohol (SF / TA-PVA) tissue adhesive gel prepared by the present invention has a gel time of 5 minutes, contains nanofibers in the structure, has good mechanical properties and degradability, and can remain stable in PBS at 37°C;

[0031] (2) The SF / TA-PVA adhesive gel loaded with Gen also exhibited effective bactericidal effects in vitro. The bFGF released by SF / TA-PVA promoted cell proliferation and attachment. The combination of Gen and bFGF stimulated protein synthesis in L929 fibroblasts, which has potential applications in postoperative wound repair.

[0032] (3) The present invention has low requirements for experimental instruments, the method is simple and easy to operate, and the obtained tissue adhesive gel has no obvious difference in performance and good uniformity. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the appearance of the PVA / SF-TA adhesive obtained in Example 1 of the present invention after being tested on human skin.

[0034] Figure 2 The morphological structure of the PVA / SF-TA adhesive obtained in Example 1 of the present invention under a scanning electron microscope (SEM) is shown.

[0035] Figure 3 The functional groups of the tissue adhesive were detected by Fourier transform infrared spectroscopy (FTIR) of the product obtained in Example 1 of the present invention.

[0036] Figure 4 The product obtained in Example 1 of the present invention was analyzed by X-ray diffraction (XRD) to analyze the crystal structure of SF and PVA after TA modification.

[0037] Figure 5 The adhesion of the tissue adhesive obtained in Example 1 of the present invention.

[0038] Figure 6 This is the release curve of gentamicin sulfate loaded by the tissue adhesive obtained in Example 1 of the present invention.

[0039] Figure 7 This is the release curve of the bFGF growth factor loaded by the tissue adhesive obtained in Example 1 of the present invention.

[0040] Figure 8 The antibacterial property of the tissue adhesive obtained by Example 1 of the present invention was tested with Staphylococcus aureus.

[0041] Fig. 9 The cell survival and migration of L929 fibroblasts on tissue adhesive 3 days after the product obtained in Example 1 of the present invention was grown.

[0042] Fig.10 This is the protein synthesis of L929 fibroblasts, the product obtained in Example 1 of the present invention, on days 7, 14 and 21. DETAILED DESCRIPTION

[0043] The following examples provide those of ordinary skill in the art with how to make and evaluate the present invention, which are merely exemplary of the present disclosure and do not define the scope of limitation. Although efforts have been made to ensure the accuracy of numerical values ​​(e.g., amounts, temperatures, etc.), some errors and deviations should be considered. Unless otherwise stated, temperatures are in ° C or at ambient temperature.

[0044] Embodiment 1

[0045] The SF powder was stirred and dissolved in ultrapure water to prepare a 2wt% SF solution. The TA powder was dissolved in ultrapure water, stirred to prepare a 10wt% TA solution, and the pH was adjusted to 6.5, and then slowly added to the 2wt% SF solution, and the final ratio of the two was 1:1.25. After 30 minutes, SF / TA began to aggregate and precipitate. The excess TA was washed and removed with ultrapure water several times, and the SF / TA precipitate was frozen in a -80℃ refrigerator, freeze-dried to obtain a solid and ground into SF / TA powder for use.

[0046] The experiment was divided into four groups, including SF / TA-PVA, SF / TA-PVA@Gen, SF / TA-PVA@bFGF and SF / TA-PVA@GenbFGF, to compare the performance differences of SF / TA-PVA tissue adhesive gels with different components.

[0047] Dissolve 0.6g PVA in 10mL ultrapure water, stir at 80℃ for 30min to obtain 6wt% PVA solution, and cool to 37℃. Take 1mL PVA solution as A solution; take 1mL PVA solution and add 10mg Gen as B solution; take 1mL PVA solution and add 1ug bFGF as C solution; take 1mL PVA solution and add 10mg Gen and 1ug bFGF as D solution.

[0048] Take 10 g of SF / TA powder and add it to liquid A to obtain SF / TA-PVA group;

[0049] 10 g of SF / TA powder was added to solution B to obtain the SF / TA-PVA@Gen group;

[0050] 10 g of SF / TA powder was added to liquid C to obtain the SF / TA-PVA@bFGF group;

[0051] Take 10 g of SF / TA powder and add it into liquid D to obtain the SF / TA-PVA@GenbFGF group.

[0052] Figure 1 The appearance of SF / TA-PVA adhesive after being tested on human skin is shown. The morphology and structure of tissue adhesive in each group are shown in Figure 2. Figure 2 shown. Figure 2The morphological structure of each group of tissue adhesive gel was observed by scanning electron microscopy (SEM), and the samples were fixed with carbon sheet glue before operation. The SEM image in a shows that the interconnected pores of SF / TA-PVA gradually disappeared and nanofibers were formed. Obvious fibril assembly was found in SF / TA-PVA@Gen. SF / TA-PVA@bFGF and SF / TA-PVA@GenbFGF showed heterogeneous structures between nanofibers and pore walls.

[0053] Figure 3 Fourier transform infrared spectrometer (FTIR) was used to analyze the interaction between SF / TA-PVA, gentamicin, and bFGF functional groups. The characteristic peak of OH stretching representing hydrogen bonding was found in all groups. After SF was modified with TA, there was an obvious hydrogen bonding peak and β-sheet structure formation in SF in the SF / TA-PVA group. After loading gentamicin and basic fibroblast growth factor, since these two substances also interacted with silk fibroin through hydrogen bonding, the strong hydrogen bonding shifted to the peak. In addition, Figure 4 The X-ray diffraction (XRD) analysis of the crystal structures of SF and PVA after TA modification showed that the mixture of SF, TA and PVA promoted the formation of SF crystalline structure and PVA semi-crystalline structure.

[0054] Figure 5 The pig skin was fixed with acrylic sheets, and the tissue adhesive gels of each group were attached to the pig skin before testing, showing the mechanical properties of tissue adhesive gels with different components. SF / TA-PVA@Gen has good adhesion and flexibility. The mechanical properties of SF / TA-PVA are higher than those of SF / TA-PVA@Gen and SF / TA-PVA@GenbFGF.

[0055] Figure 6 and Figure 7 At different time points, including 1, 4, 8, 12, 24 and 48 hours, all groups of tissue adhesive gel were immersed in 2 ml of PBS. At each time point, the cumulative release of gentamicin in 500 microliters of solution was terminated and 500 microliters of fresh PBS were replaced. The amount of gentamicin released at each time point was analyzed using a gentamicin ELISA kit (Jining Shiye) and an ELISA kit (mouse bFGF ELISA kit, Jining Shiye) to detect and analyze the release of Gen and bFGF in tissue adhesive gel. The results showed that Gen and bFGF were slowly released from the tissue adhesive gel. The slow release mode inhibited bacterial growth and was beneficial to promote the formation of new tissue during wound healing.

[0056] Figure 8The antibiotic function of tissue adhesive gel was tested with Staphylococcus aureus (S. aureus). The zone of inhibition (ZOI) and percentage of bactericidal effect of tissue adhesive gel were tested after 24 hours. The results showed that the antibacterial effect of SF / TA-PVA@GenbFGF group was better than that of other groups. The antibacterial effects of SF / TA-PVA@Gen and SF / TA-PVA@bFGF were similar, but both were higher than those of SF / TA-PVA group.

[0057] Fig. 9 L929 fibroblasts were used to test the biocompatibility of tissue adhesives. The cells were cultured on the surface of the material, and the cell survival rate was detected by calcein AM staining on the third day. Compared with SF / TA-PVA and SF / TA-PVA@Gen, the cell migration ability of SF / TA-PVA@bFGF and SF / TA-PVA@GenbFGF was stronger. Protein synthesis is a sign of new tissue formation in soft tissues. Fig.10 The protein synthesis efficiency of L929 fibroblasts in each group on tissue adhesive gel was evaluated using a bicinchoninic acid protein assay kit (BCA). The results showed that on the 7th day, the protein synthesis in the SF / TA-PVA@bFGF group was higher than that in the other groups. From the 7th day to the 14th day, the protein synthesis content increased rapidly, and the SF / TA-PVA@Gen and SF / TA-PVA@GenbFGF groups were higher than those in the other groups, and the protein content of all groups decreased on the 21st day.

[0058] Based on the above results, the SF / TA-PVA@GenbFGF group has better performance in all aspects and is more suitable for wound tissue healing.

[0059] Embodiment 2

[0060] The SF powder was stirred and dissolved in ultrapure water to prepare a 2.3wt% SF solution. The TA powder was dissolved in ultrapure water, stirred to prepare a 9% TA solution, and the pH was adjusted to 6.0, and then slowly added to the 2.3% SF solution, and the final ratio of the two was 1:1.2. After 30 minutes, SF / TA began to aggregate and precipitate. The excess TA was washed and removed with ultrapure water several times, and the SF / TA precipitate was frozen in a -80℃ refrigerator, freeze-dried to obtain a solid and ground into SF / TA powder for use.

[0061] 0.5 g PVA was dissolved in 10 mL ultrapure water, and stirred at 80° C. for 30 min to obtain a 6% PVA solution. After cooling to room temperature, 15 mg Gen and 3 ug bFGF were added to 1 mL of the PVA solution.

[0062] Then 5 g of SF / TA powder was added to the above PVA solution loaded with Gen and bFGF to obtain the desired tissue adhesion gel (SF / TA-PVA@GenbFGF).

[0063] The SF / TA-PVA tissue adhesive gel prepared in Example 2 has similar wound healing, antibacterial and cell proliferation promoting effects as those in Example 1.

[0064] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a silk fibroin-doped tannic acid-polyvinyl alcohol tissue adhesive gel, characterized in that: The steps include: 1) preparing silk fibroin doped with tannic acid powder; 2) PVA is dissolved in ultrapure water to prepare a PVA solution, and after the temperature is lowered, gentamicin sulfate Gen and basic fibroblast growth factor bFGF are added to the PVA solution respectively, and stirred until dissolved to prepare a PVA solution loaded with Gen and bFGF; 3) The silk fibroin-doped tannic acid powder prepared in step 1) and the PVA solution loaded with Gen and bFGF prepared in step 2) are mixed at room temperature to obtain the desired SF / TA-PVA tissue adhesive gel.

2. The preparation method according to claim 1, characterized in that: The step 1) specifically includes: 1.1) Preparation of silk fibroin SF solution SF powder is dissolved in ultrapure water and then released into SF solution; 1.2) Preparation of tannic acid TA solution TA powder was dissolved in ultrapure water and the pH value was adjusted to prepare TA solution; 1.3) Preparation of silk fibroin doped with tannic acid SF / TA powder The TA solution was added dropwise to the SF solution and the mixture was allowed to stand. After removing the excess TA, the mixture was freeze-dried and ground into SF / TA powder for later use.

3. The preparation method according to claim 2, characterized in that: In the step 1.1), the concentration of the SF solution is 1.50-2.50 wt %.

4. The preparation method according to claim 2, characterized in that: In the step 1.2), the concentration of the TA solution is 8-12 wt %, and the pH range is 5.50-6.

50.

5. The preparation method according to claim 2, characterized in that: In the step 1.3), the volume ratio of the TA solution to the SF solution is 1:1.20-1.30; and the standing time is 25-40 minutes.

6. The preparation method according to claim 1, characterized in that: In the step 2), the PVA dissolution temperature is 75-85°C, the PVA solution is cooled to 37°C or below and then Gen and bFGF are added, the concentration of the PVA solution is 5-7wt%, the concentration of Gen in the PVA solution is 1-50mg / mL, and the concentration of bFGF in the PVA solution is 1-5ug / mL.

7. The preparation method according to claim 1, characterized in that: In the step 3), the mass ratio of PVA to SF / TA powder in the solution is 1:33-83.

8. The silk fibroin-doped tannic acid-polyvinyl alcohol tissue adhesive gel prepared by the method according to any one of claims 1 to 7.

9. Use of the silk fibroin doped with tannic acid-polyvinyl alcohol tissue adhesive gel according to claim 8 in the preparation of a drug for promoting wound tissue healing.

10. Use of the silk fibroin doped tannic acid-polyvinyl alcohol tissue adhesive gel according to claim 8 in the preparation of wound repair drugs.